Contemporary in-hospital and long-term prognosis of patients with acute ST-elevation myocardial infarction and chronic kidney disease in Germany. (14th October 2021) - Engelbertz, C; Koeppe, J; Feld, J; Makowski, L; Kuehnemund, L; Fischer, A J; Lange, S A; Guenster, C; Droege, P; Ruhnke, T; Gerss, J; Freisinger, E; et al.
Abstract: Background: Although acute myocardial infarction (AMI) incidence and mortality have decreased over the last decades, survival rates of AMI patients remain rather stable. About 25% of patients with ST-elevation myocardial infarction (STEMI) suffer from chronic kidney disease (CKD). Purpose: We sought to determine short- and long-term mortality in STEMI patients with different stages of CKD. Methods: We identified all patients who were hospitalised with a main diagnosis of STEMI between 2010 and 2017 from the dataset of the Federal Association of the Local Health Insurance Funds (Allgemeine Ortskasse), Germany. The patients were grouped according to their CKD stage at index hospitalisation. We analysed concomitant diseases, in-hospital treatment and complications. Overall survival was analysed using Kaplan Meier methods and predictors for overall survival were identified by Cox regression analysis. Results: A total of 175, 187 patients were identified with an index hospitalisation for STEMI, thereof 137, 682 (78.6%) patients without CKD, 8, 347 (4.8%) patients with CKD stage 2, 20, 459 (11.7%) patients with CKD stage 3, and 4, 960 (2.8%) patients with CKD stage 4. The CKD stages 1, 5 and 5d (dialysis dependent CKD) each comprised less than 1, 500 patients (<1.0%). STEMI patients with CKD were older and had more often cardiovascular risk factors, e.g. diabetes (no CKD: 33.2% vs CKD stage 5: 66.1%, p<0.001). Overall, patients with CKD received percutaneous coronary interventions (no CKD: 84.4% vs CKD stage 4: 62.0%, p<0.001) less frequently, and suffered more often from complications like shock (no CKD: 12.5% vs. CKD stage 5: 27.7%, p<0.001) or requirement of invasive/non-invasive ventilation (no CKD: 17.3% vs. CKD stage 5: 42.7%, p<0.001) than patients without CKD. With increasing CKD stages, patients were more likely to die within 30 days after STEMI (30-day mortality no CKD: 13.7% vs. CKD stage 5d: 37.2%, p<0.001). Kaplan-Meier estimates showed dramatically decreasing survival with decreasing renal function (Figure 1). Multivariable time-dependent Cox regression analysis for overall survival showed that the CKD stages 4, 5 and 5d, as well as chronic limb threatening ischemia (CLTI) were associated with a higher risk for death (CKD stage 5d: hazard ratio (HR) 5.64; 95% CI 5.42–5.86; CKD stage 5: HR 2.55; 95% CI 2.37–2.73; CKD stage 4: 1.72; 95% CI 1.66–1.78; CLTI: 2.06; 95% CI 1.98–2.13; all p<0.001). Conclusion: CKD is a frequent co-morbidity in patients with STEMI which is associated with a devastating prognosis especially for patients with advanced CKD stages. More research is needed to gain evidence on optimized treatment strategies for patients with STEMI and concomitant CKD in this highly vulnerable cohort. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The project upon which this publication is based was funded by The Federal Joint Committee, Innovation Committee (G-BA, Innovationsfonds, number 01VSF18051).